The Effect of Different Polishing Methods and Composite Resin Thickness on Temperature Rise of Composite Restorative Materials - Parvin MirzaKoucheki Boroujeni; Nazanin Daneshpour; Maryam Zare Jahromi (Islamic Dental Association of Iran, 2013)
Background and Aim : Along with improvements in aesthetics and longevity of restorations, finishing and polishing, can produce potentially injurious temperature rise within the pulp chamber. The purpose of the current study was to find whether different polishing methods and thickness of composites have any effect on temperature rise of composite restorative materials .   Materials and Methods : Sixty composite resin specimens 9 mm in diameter were prepared and assigned to three experimental groups with three sample thicknesses (2, 3 and 4mm). Each group was divided into four subgroups randomly. Polishing in subgroups 1 and 2 (continuous and intermittent dry polishing) and subgroups 3 and 4 (continuous and intermittent wet polishing) was carried out with a slow speed contra-angle hand piece at a medium speed for 120 seconds in a roll on motion. Immediately after polishing, temperature was measured on the top and bottom surface of each sample using a laser thermometer. One and two way ANOVA, Duncan, and paired T-test was used to analyze the data .   Results: The mean temperature rise after polishing in different methods was significant continuous dry polishing produced the maximum temperature rise. In addition, increasing the thickness of composite resin up to 4mm did not significantly affect thermal transfer from the top surface to the base during polishing .   Conclusion : Copious use of water coolant during finishing and polishing procedures is considered a simple and effective method for pulpal protection. Increasing the thickness of composite resin does not have a significant role in compensating the heat generated during polishing procedure .